The Effect Of ESG (Environmental, Social And Governance) Performance On Company Value And Company Performance - Elika Mahsa Delvina; Raudhatul Hidayah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study aims to prove that ESG performance has a positive and significant effect on firm value (Tobins'Q) and firm performance (ROA) in non-financial sector public companies on the Indonesia Stock Exchange in 2017-2021. Purposive sampling was used to select 34 companies as samples with a total of 170 observations during the five years of research. The method used is a quantitative approach with secondary data from the Refinitiv Eikon Database, and the regression analysis was performed using IBM SPSS version 21. The results show that companies that focus on ESG aspects tend to achieve better company value and company performance. ESG performance provides public legitimacy that increases trust, support and acceptance from various stakeholders, including investors, consumers, governments, communities and other groups. The research recommendation is for companies to integrate ESG aspects in business decisions and for investors to consider ESG aspects in investment decisions.